2004
DOI: 10.1080/08038740410005758
|View full text |Cite
|
Sign up to set email alerts
|

War, women and health

Abstract: Wars increasingly target civilian populations and cause severe health problems in those targeted. It also creates a militarization and masculinization of society and exacerbates discrimination against women, for example by intensifying women's exclusion from the public sphere and rendering access to health services more difficult. Sexual violence is a clear example hereof and may take many forms, for example as rape, sexual mutilation, forced abortion, or forced prostitution. The vulnerability of women is rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
1
4
0
1
Order By: Relevance
“…Similar studies in the past have also revealed an increase prevalence of depression among victims of violent conflicts [9,10,12,13]. The factors that could be responsible here would include loss of loved ones, sources of livelihood and properties putting the victims in a state of helplessness and hopelessness [18]. About one tenth of our subjects had dysthymia.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Similar studies in the past have also revealed an increase prevalence of depression among victims of violent conflicts [9,10,12,13]. The factors that could be responsible here would include loss of loved ones, sources of livelihood and properties putting the victims in a state of helplessness and hopelessness [18]. About one tenth of our subjects had dysthymia.…”
Section: Discussionsupporting
confidence: 79%
“…This figure is about 3 times the 3.7% prevalence of dysthymia in the general population [19]. Persisting low level of depressive symptoms could be adduced to a state of pervasive socio-economic decline, increased household strain faced by victims, loss of a family member or property that usually accompanies violent conflicts [18]. The report of the study conducted by Agbir and colleagues [12] also yielded a similar result.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Many aspects of war disproportionately affect women and their health. Social upheaval and societal changes in the wake of war may subordinate women and deprioritize their health, as well as render them more likely to experience violent acts such as rape and sexual assault [18]. Sociocultural norms of collectivist societies may also affect women's coping responses in the wake of traumatic events, leading to further deleterious effects on their health and wellbeing [19].…”
Section: Introductionmentioning
confidence: 99%
“…En cuanto a la salud sexual, ha sido reportado que las disfunciones sexuales suelen encontrarse en comorbilidad con alteraciones de la salud mental (SM), en población general 13 , y aún más en mujeres expuestas a confrontaciones armadas 11 , 14 o a violencia sexual en el marco del conflicto armado 15 , 16 . Existen publicaciones internacionales relativas a mujeres militares expuestas a eventos violentos de alta intensidad en guerras, quienes presentaron disfunciones sexuales entre un 12,7 y un 62,3 % 11 , 14 , que fueron significativamente más frecuentes entre quienes tenían comorbilidad con un trastorno por estrés postraumático respecto a quienes no habían recibido tal diagnóstico (p = 0,022) 14 .…”
Section: Introductionunclassified